Nutrition education : strategies for improving nutrition and healthy eating in individuals and communities - Ballam, Roy; Black, Maureen M.; Capanzana, Mario V.; Crawford, Patricia B.; Dattilo, Anne M.; Delichatsios, Helen K.; Story, Mary T. (Basel, Switzerland : Karger, 2020)
Nutrition education may be defined as a combination of educational tactics accompanied by physical or environmental supports, the purpose of which is to encourage voluntary adoption of foods and other lifestyle behaviors that are beneficial to health. This book highlights the importance of nutrition education as an integral part of day-to-day life. The first part takes an in-depth look at what nutrition education is and how it can be used to influence various target populations. The second part explores the complexities of eating behavior, underscoring the importance of early childhood as a critical time for intervention. The final part focuses on nutrition education in medical schools, highlighting the latest educational technologies being used in curricula, as well as methods for bringing nutrition to the clinic. The insights presented in this book cover the basis of how nutrition interventions can be designed and delivered to improve food choices and, ultimately, an individual's health. The publication will be of great interest for educators, pediatricians, dietitians, public health, professionals, and policy makers.
La función de los autores fue determinada por el catalogador
Keywords: EDUCACIÓN NUTRICIONAL